A 27-country test of communicating the scientific consensus on climate change - Većkalov, Bojana; Geiger, Sandra J; Bartoš, František; White, Mathew P; Rutjens, Bastiaan T; van Harreveld, Frenk; Stablum, Federica; Akın, Berkan; Aldoh, Alaa; Bai, Jinhao; Berglund, Frida; Bratina Zimic, Aleša; et al. (Nature human behaviour, 2024)
Communicating the scientific consensus that human-caused climate change is real increases climate change beliefs, worry and support for public action in the United States. In this preregistered experiment, we tested two scientific consensus messages, a classic message on the reality of human-caused climate change and an updated message additionally emphasizing scientific agreement that climate change is a crisis. Across online convenience samples from 27 countries (n = 10,527), the classic message substantially reduces misperceptions (d = 0.47, 95% CI (0.41, 0.52)) and slightly increases climate change beliefs (from d = 0.06, 95% CI (0.01, 0.11) to d = 0.10, 95% CI (0.04, 0.15)) and worry (d = 0.05, 95% CI (-0.01, 0.10)) but not support for public action directly. The updated message is equally effective but provides no added value. Both messages are more effective for audiences with lower message familiarity and higher misperceptions, including those with lower trust in climate scientists and right-leaning ideologies. Overall, scientific consensus messaging is an effective, non-polarizing tool for changing misperceptions, beliefs and worry across different audiences.
Keywords: Public Opinion; komunikace; mužské pohlaví; ženské pohlaví; Climate Change; dospělí; Humans; Trust; Communication; Consensus; Female; Adult; důvěra; Male; klimatické změny; lidé; konsensus; veřejné mínění